FACTORS OF ANTENATAL CARE SERVICES ON THE LEVEL OF SATISFACTION OF PREGNANT WOMEN AT HADI HUSADA HOSPITAL - Sri Malemna Br Barus; Selvi Puspan Sari (Benih : Journal of Midwifery, 2025)
Antenatal care services are health services by trained health workers for mothers during their pregnancy, implemented according to midwifery service standards. The initial survey conducted by researchers included 10 pregnant women who visited antenatal care, 7 of whom stated they were satisfied and 3 of whom stated they were less satisfied. The purpose of the study was to determine the factors that influence the level of satisfaction of pregnant women with antenatal care services. Method: This type of research is quantitative with a cross-sectional study approach. This research was conducted at Hadi Husada General Hospital. The population in this study were 30 third-trimester pregnant women who underwent examinations at Hadi Husada General Hospital with a total sampling technique so that the sample in this study was 30 pregnant women. The method of data collection used a questionnaire. Statistical analysis used the chi-square test. Research Results: Shows that there is a relationship between antenatal care services and the level of satisfaction of pregnant women with a p-value of 0.001 (<0.005). Conclusion: It was found that there is a relationship between antenatal care services and the level of satisfaction of pregnant women.